Pembentukan Karakter Siswa melalui Pendidikan Agama Islam di Sekolah Menengah Pertama - Sri Mahyuni (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to examine the role Islamic religious education in shaping students’ character at the junior high school level. Islamic education focuses not only on cognitive aspects but also on developing students’ attitudes and behaviors in accordance with Islamic moral values. This research employs a qualitative approach using a case study method at a public junior high school. Data were collected through observation, interviews with Islamic education teachers, and documentation of religious activities at the school. The findings indicate that Islamic education plays a significate role in character development, particularly in promoting discipline, honesty, responsibility, and tolerance. Activities such as congregational prayers, greeting habits, and classroom moral instruction have proven effective in instilling character values. Therefore, Islamic religious education contributes meaningfully to the holistic character formation of students within the school environment.